How does a small area cause big syndromes? A case report of a patient with one-and-a-half syndrome and MRI review of the anatomical pathways involved in causing different pontine neuro-ophthalmological syndromes - Gonzalez-Arocha Carla (Elsevier, 2021)
Purpose: To describe the clinical symptoms, anatomical location of the injury and different etiologies of one-and-a-half syndrome and its variants. Observations: A small lesion to the brainstem can cause complex syndromes that involve the disfunction of different nuclei and pathways. A 52-year-old man presented with sudden onset of diplopia characterized by horizontal gaze palsy and internuclear ophthalmoplegia (INO). With these clinical characteristics, the patient was diagnosed with the one-and-a-half syndrome. Neuroimaging revealed an acute/subacute ischemic lacunar event in the pontine tegmentum. The one-and-a-half syndrome is described as a horizontal gaze palsy in one direction (damage to the paramedian pontine reticular formation [PPRF] or the VI nerve nucleus) and an internuclear ophthalmoplegia in the other direction (damage to the medial longitudinal fasciculus). Along with the traditional description, the closed anatomical proximity with other nuclei and pathways makes possible the appearance of other more complex syndromes that have been grouped as the one-and-a-half syndrome and its variants. Conclusions and importance: A detailed clinical neuro-ophthalmologic examination, along with a clear understanding of the neuroanatomical pathways, gives clinicians a good diagnostic opportunity to determine the precise location of injuries to the brainstem.